The Poetical, Structural and Semantical Nature of Similes - Jumanazarov, Umurzoq Abdurazzokovich; Jumanazarova, Guljahon Umirzakovna; Jumanazarova, Dilnoza Umirzakovna (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, it has been recognized that the field of linguoculturology in world linguistics is a leading direction in the study of the language system and one of its objects of study are linguacultural units. In particular, in the scientific literature related to this field, it is noted that similes, metaphors, metonymy, proverbs and phrases as linguacultural units of a particular language represent the national worldview of a nation. D.Khudoyberganova also gave a valid conclusion in this regard: “Such cultural units are evidence of the mentality of an ethnos, as well as the level of expression of actual reality through language. They also reflect the social and spiritual development of people” [1]. We also agree with the comments in this regard that the language of folk epics includes symbols, similes, metaphors, metonyms, adjectives, artistic repetitions, paremiologically units and the art of saj’ prose, phraseology, riddles, words related to customs and rituals, informal elements of speech (swearing, cursing, etc.) are also linguacultural units. The study of the language of the epics of Fazil the Poet shows that the attitude of the poet to the behavior of the epic heroes, their appearance and condition, or to a trait of an object manifests itself through associative thinking in the linguacultural units we are referring to. We first observe this in the skill of the folk poet in the use of similes.